Optimasi Jadwal Penjagaan Lembaga Pemasyarakatan Kelas IIB Pasir Pengaraian dengan Metode Goal Programming - Sita Pramutia; Yusmet Rizal (UNIVERSITAS NEGERI PADANG, 2020)
Abstract— Increasing the number of prisoners as well as the lack of security guards is a very serious matter faced by a prison. Events that have occurred where a security officer was threatened with a firearm in Pasir Pengaraian makes every correctional institution must always be vigilant and can regulate the security of correctional institutions in the right way. Prison Class IIB Pasir Pengaraian has limitations in the number of guards so that it requires the right method in making a guard schedule. The purpose of this study is to determine the shape of the model and the results of the Optimization of Class IIB Pasir Pengaraian Prison Guard Schedule with Goal Programming Method. Goal Programming Method is a method of solving linear programming cases that have more than one target to be achieved. By completing the scheduling model using the help of LINGO 17.0 software, the results show that with the Goal Programming method minimum morning shift guards are met, 7 people do not meet the minimum day shift guard, 4 people do not meet the minimum night shift guard, and no guards get a holiday-enter-holiday pattern. Keywords — Goal Programming, Prison, Scheduling.